Christian Faith, Formation and Education (Springer International Publishing, 2018)
This book discusses the relationship between faith, formation and education. Rooted in a variety of discourses, the book offers original insights into the education and formation of the human person, both theoretical and practical. Issues are considered within a context of contemporary tensions generated by an increasingly pluralist society with antipathy to religious faith, and debated from interdenominational Christian perspectives. Including chapters by an international team of experts, the volume demonstrates how Christian faith holds significance for educational practice and human development. It argues against the common assumption that there can be a neutral approach to education, whilst at the same time advocating a critical dimension to faith education. It brings fresh thinking about faith and formation, which demands attention given the fast-changing political, educational and socio-cultural forces of today. It will appeal to students and researchers involved in Christian educational practice. .